PERAN DAN FUNGSI BAHASA DALAM PEMASARAN PRODUK DI ERA GLOBALISASI - Arif ma’mun rifa’i (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2021)
abstract Communicative competence is a person's ability to communicate in accordance with the topic, area, field up to greet the other person. Communicative competence includes the knowledge that the speakers have about what underlies the correct language behavior or speech behavior, and about what constitutes effective language behavior The communicative component is the ability to distinguish social markers or carry other meanings and meanings that are variants in certain situations. In the globalization era with the technological developments, marketers of the product are demanded to be able and wiser in assembling words according to different contexts and cultures in the global market segment. The role and function of language cannot be negated from human being, both are closely attached and cannot be separated each others. The choice of part of language as a communication tool in marketing can determine how a product can be explained through language that can attract consumers. It proves that the role of language is so important to study, because through its language function has meaning that gives information clearly as guidence that the product is the best alternative among product competitions in the global segment. Key words : role and function of language, product marketing, and globalization era